2022
DOI: 10.3390/ijms23169178
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell Neutral Sphingomyelinase 2 in the Release of Exosomes and Vascular Calcification

Abstract: Vascular calcification (VC) is the pathological precipitation of calcium salts in the walls of blood vessels. It is a risk factor for cardiovascular events and their associated mortality. VC can be observed in a variety of cardiovascular diseases and is most prominent in diseases that are associated with dysregulated mineral homeostasis such as in chronic kidney disease. Local factors and mechanisms underlying VC are still incompletely understood, but it is appreciated that VC is a multifactorial process in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…In this study, we demonstrated that muscle cell-derived exosomes induced the neurite outgrowth in neuronal cells. Although there have been studies on the effects of adipocyte-derived exosomes on skeletal muscle [ 23 ] and the involvement of exosomes in muscle–kidney interactions [ 24 ], there are few reports on the functionality of exosomes produced by muscle cells [ 25 ]. In particular, results so far suggest that carnosine may induce the interaction between intestinal cells, muscle cells and neuronal cells via exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that muscle cell-derived exosomes induced the neurite outgrowth in neuronal cells. Although there have been studies on the effects of adipocyte-derived exosomes on skeletal muscle [ 23 ] and the involvement of exosomes in muscle–kidney interactions [ 24 ], there are few reports on the functionality of exosomes produced by muscle cells [ 25 ]. In particular, results so far suggest that carnosine may induce the interaction between intestinal cells, muscle cells and neuronal cells via exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Phingomyelin phosphodiesterase 3 (SMPD3, also known as Neutral sphingomyelinase 2,nSM2) has been shown to regulate the release of exosomes [ 228 ]. Increased SMPD3 expression under high extracellular calcium promotes the secretion of calcifying exosomes [ 17 ], and inhibition of SMPD3 expression by Barley-ß-glucans prevents VSMC calcification [ 229 ].…”
Section: The Crosstalk In Vascular Calcificationmentioning
confidence: 99%
“…Phenotypic conversion of VSMC is a key aspect of VC development. VSMC can be converted from a contractile phenotype to a synthetic phenotype, facilitating the release of EVs and converting them to a calcified state ( 37 ). Calcified EVs contain fewer inhibitors of calcification, and when released into the ECM, it tends to aggregate and form microcalcifications in areas of sparse collagen.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%